Unveiling the Hidden Causes: Epidemiology and Risk Factors Behind Hair Fall - Muhammad Mohsin Abbas; Syeda Aneela Azad; Nazir Suliman; Muhammad Ibrar Shinwari; Dr. Akif Saeed Ch; Fatima; Raza Hassan Tariq; Ussama Hafeez (Policy Journal of Social Science Review, 2026)
Individuals of all ages and genders are frequently affected by hair loss, a problem with both physical and psychological impact. This article aims to provide a basis for understanding the epidemiology and risk factors associated with hair loss to promote effective prevention, early diagnosis, and treatment. Reasons for the global prevalence and distribution of hair loss (varying by age, sex, race, heredity, and environmental factors) have not been well established, but numerous forms of hair loss exist, including androgenetic alopecia, telogen effluvium, and alopecia areata, which are the more commonly diagnosed. There are many risk factors that lead to an excessive amount of hair loss; however, some of the most common include hereditary predisposition, hormone-related changes, nutritional deficiency, chronic illness, psychological stresses, medications, autoimmune diseases, and infections of the scalp. In addition to the aforementioned medical risk factors, several modifiable risk factors exist among individuals, such as dietary habits, smoking, lack of sleep, pollution, and chemical hair treatment use, which may increase the likelihood of developing hair loss. Women have additional contributing risk factors to hair loss that include pregnancy, menopause, and endocrine disorders (e.g. polycystic ovary syndrome), whereas the primary contributing risk factor to hair loss in men is their sensitivity to androgens. Other recent studies suggest that oxidative stress, inflammation, and the microenvironment of the hair follicle may contribute to the progression of the disease. By understanding these epidemiological patterns and modifiable risk factors, targeted prevention and personalized treatment options can be developed. Keywords: Hair fall, Epidemiology, Risk factors, Androgenetic alopecia, Telogen effluvium, Alopecia areata, Genetic predisposition, Nutritional deficiency, Hormonal imbalance, Lifestyle factors